Relationship between changes in core body temperature in lambs and post-slaughter muscle glycogen content and dark-cutting - Pighin, Darío Gabriel; Brown, W.; Ferguson, D.M.; Fisher, A.D.; Warner, R.D. (2018)
Pre-slaughter stress may decrease muscle glycogen content, a key element for a suitable low ultimate pH and prevention of dark-cutting meat. Body temperature monitoring is a tool used in research on animal stress, as an indicator of stress events. Possible relationships between body temperature of sheep and post-mortem muscle glycogen were investigated in this study. Body temperature was measured with intravaginal loggers inserted into each animal at 3 days pre-slaughter, to record body temperature every 3 min over a period of 3 days. Blood samples were collected from each animal at exsanguination for measurement of glucose and lactic acid concentrations. The muscle content of glycogen and lactic acid were determined in samples of M. longissimus collected at the level of the 13th rib, at 1 h post-slaughter. A plot of body temperature versus time showed a rise in body temperature from all animals during events such as mustering, loading onto the truck, unloading at the abattoir, during pre-slaughter handling and at slaughter. Pearson’s correlation coefficients were determined between (1) the main temperature increments occurring between farm and slaughter; and (2) post-slaughter muscle glycogen and lactate levels. A significant negative correlation was detected between elevation in core body temperature due to physical stress of sheep and muscle glycogen levels at slaughter. A low correlation was detected between body temperature and blood glucose or lactate concentrations. Further research should examine the relationship between core body temperature and meat quality in order to better understand the complex relationship between animal stress and meat quality.